Resilience in post-socialist context: The case of a watermelon producing community in Hungary - Lendvay, Márton (Hungarian Geographical Bulletin, 2016)
The aim of this paper is to test whether the concept of resilience can be applied to rural communities in postsocialist transition countries such as Hungary. Resilience, a concept engaged with the dynamics of change, has gained popularity in recent years following the post-2008 crisis and has become a core theme of academic, policy and lay discourses in the Anglo-Saxon world. The ongoing processes of socio-economic transition within the post-socialist environment have also att racted wide attention in the past decades, although not within the frameworks of resilience thinking. The concept of resilience is missing from post-socialist discourses and has not been applied to rural communities before in an Eastern European context, although the nature of post-socialist transition characterised by complexity, cross-scalar processes and multiplicity of actors involved make it an especially suitable field for resilience studies. In this paper, we aim to flag the potential directions and successful application of the concept of resilience both as a research topic and as a tool for researchers of the post-socialist space while we caution for the potential pitfalls and misuses of the concept and critically analyse aspects that attracted wide debates. We illustrate how rural community resilience may be conceptualised on the example of the watermelon producing community of Medgyesegyháza, Hungary.